Investigação de plantas medicinais e tóxicas em Pelotas-RS e determinação da atividade antifúngica frente a Malassezia pachydermatis - Giordani, Claudia (2013)
The rescue and use of medicinal plants have been gaining space in human and veterinary medicine, as treatment and prophylaxis of diseases. In the treatment of mycosis, there is still issues regarding the limited amount of drugs and the occurrence of resistance, adverse reactions and relapses. Thus, the objective was to conduct a survey of medicinal plants and toxic found in the region of the Veterinary Clinic-Federal University of Pelotas, organize an instructional manual of the studied plants and uses in animal health, and to determine the antifungal effect of plant extracts on clinical isolates of Malassezia pachydermatis. In the survey, animal owners in the Veterinary Ambulatory were interviewed and visited. There were 111 interviews, which 74 species cited for medical use but the minority used them in animals. With respect to toxic plants 20 species were observed, but only six were reported by the population, and from the results in the survey was made a manual on plants. To evaluate the antifungal activity were tested six hydroalcoholic extracts of Aroeira, Carqueja, Erva-de-bicho, Lanceta, Pitangueira e Rabo-de-lagarto, the techniques microdilution and disk diffusion against M. pachydermatis isolated from dogs (dermatitis=38, otitis=10). The extracts that resulted in higher activity were Aroeira, Erva-de-Bicho and Pitangueira. From these results, we can see the importance of further studies of the activities of plants to determine more precisely its action and toxicity. With this study concludes that there are many medicinal and toxic species distributed in the region of the Veterinary Clinic-UFPel, but is still scarce use of medicinal plants in animal, and that the hydroalcoholic extracts of Aroeira, Erva-de-bicho and Pitangueira had action on M. pachydermatis, opening the possibility of numerous studies in veterinary medicine.